Reproducibility of the dynamic balance test of lower limbs with reduction of the body weight in individuals with knee osteoarthritis - Saulo da Cunha Machado; Valter Joviniano de Santana Filho; Érika Thatyana Nascimento Santana; Viviane Nascimento Brandão Lima; Wélia Yasmin Horacio dos Santos; Walderi Monteiro da Silva Júnior; Jader Pereira de Faria Neto; Pedro José Marin; Marzo Edir da Silva-Grigoletto (Desafio Singular, 2022)
The dynamic balance of the lower limbs has shown great importance in accomplishing activities of daily living, especially for walking and maintenance in the orthostatic position. In this context, individuals with knee osteoarthritis have changes in their physical capacity, mainly due to joint changes and muscular wear. The instrument called OctoBalance® is one of the most used to evaluate this balance, which analyses four different executions of movement in the limbs. However, individuals with knee osteoarthritis cannot perform this evaluation due to the need for single limb support during movements. This study aimed to verify whether it is reproducible to perform the dynamic balance evaluation of lower limbs with a reduction of 10% of body weight through a suspension system. A cross-sectional study was carried out with 2 collections with a 48-hour interval between them, using the Lower Body Test performed with OctoBalance®. The dynamic balance test followed the protocol of 3 repetitions observing the learning factor and then 3 repetitions where the values were collected, with the suggested adaptation for all 4 diagonals in both limbs. The interclass correlation index (ICI), coefficient of variation (CV), estimative standard error (EEE) and minimum detectable difference (MDD) were calculated as indicators of reproducibility. Also, Bland-Altman Graphs were used for visual verification of the agreement between the means. Results: The reliability tests showed a very high interclass correlation through the ICI and low variation values for all the movements evaluated through the CV. The EEE and MDD calculations showed positive responses for greater reliability, and the Bland-Altman graphs showed an agreement between the means. Reproducibility was positive for the Lower Body Test with the Octobalance® platform for the evaluation of lower limb dynamic balance in women with knee osteoarthritis.